Implementation of Public Services through SI PATAS Innovation Program in Banyumas Regency, Central Java Province - Riyanti, Winda Cahya; Perdani, Titis; Sobandi, Khairu Rooijqien (Fakultas Ilmu Sosial and Ilmu Politik Universitas Jenderal Soedirman, 2023)
This study discuss the implementation of public services through SI PATAS innovation program in Banyumas Regency, Central Java Province by utilizing qualitiave research methods. Using digital democracy theory, bureaucracy must deal with new ways of providing public services. We found that street level bureaucracy (SLB) try to innovate by creating a social media based public services through Whatsapp, the so-called SI PATAS in order to make the services delivered faster and easier. However, we found that the society did not perceived this new technology based public service well as it cannot solved the issues. It imply that the experimentation from SLB through SI PATAS did not meet the demands and needs of society in getting public services easier and faster.